Prevalence and Determinants of Schistosoma haematobium and Ascaris lumbricoides Infections among Primary School Pupils in Bantaje Ward, Wukari Local Government Area, Taraba State, Nigeria - S.H., Nengean; A. K., Mijah; Yafiryau, E. P.; U. E., John-Zaka; H.I.J., Agere (Darul Yasin Al Sys, 2026)
Schistosomiasis and ascariasis remain major causes of morbidity among school-aged children in Nigeria, especially in rural areas where access to water, sanitation, and hygiene (WASH) facilities is inadequate. This study assessed the prevalence and determinants of Schistosoma haematobium and Ascaris lumbricoides infections among primary school pupils in Bantaje Ward, Wukari Local Government Area, Taraba State, Nigeria. A descriptive cross-sectional study was conducted among 384 pupils aged 5–16 years selected from six primary schools using multistage sampling. Urine and stool samples were examined microscopically for S. haematobium and A. lumbricoides using sedimentation and direct wet mount techniques, respectively. Structured questionnaires were used to collect information on sociodemographic characteristics, sanitation, water contact, and hygiene behaviours. Data were analysed using SPSS version 29, and associations were determined using chi-square tests at a significance level of p < 0.05. The overall prevalence of S. haematobium and A. lumbricoides infections were 13.3% and 16.4%, respectively. Pupils who used rivers and streams for domestic activities recorded significantly higher prevalence of S. haematobium infection (p = 0.002), while swimming and fishing were the main risk factors. For A. lumbricoides, open defecation (p = 0.001) and eating food dropped on the ground were significant determinants of infection. Treatment-seeking behaviour was generally poor, with many pupils taking no action when symptomatic. The study revealed moderate endemicity of urinary schistosomiasis and ascariasis among primary school children in Bantaje Ward, driven largely by unsafe water contact, poor sanitation, and unhygienic practices. Integrated control measures combining periodic mass drug administration with improved WASH facilities, behavioural change communication, and strengthened school-based health education are recommended to reduce infection transmission and the associated disease burden in the area.